New and future developments in microbial biotechnology and bioengineering : recent developments in trichoderma research - Gupta, Vijai Kumar; Zeilinger-Migsich, Susanne; Singh, H. B., Dr; Druzhinina, Irina S., 1974- (Elsevier, 2020)
New and Future Developments in Microbial Biotechnology and Bioengineering: Recent Developments in Trichoderma Research covers topics on-Trichoderma biodiversity, strain improvement and related researches in bioprocess technology, chemical engineering, bioremediation process, secondary metabolite production, Protein production, plant disease resistance and biocontrol technology. This book includes unique compilations of different chapters with emerging issues in the area of Trichoderma research and its related importance in the Biochemical-Industry-Agri-Food sector.